2018
DOI: 10.1007/s11027-017-9774-8
|View full text |Cite
|
Sign up to set email alerts
|

Congo Basin peatlands: threats and conservation priorities

Abstract: The recent publication of the first spatially explicit map of peatlands in the Cuvette Centrale, central Congo Basin, reveals it to be the most extensive tropical peatland complex, at ca. 145,500 km 2 . With an estimated 30.6 Pg of carbon stored in these peatlands, there are now questions about whether these carbon stocks are under threat and, if so, what can be done to protect them. Here, we analyse the potential threats to Congo Basin peat carbon stocks and identify knowledge gaps in relation to these threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 54 publications
2
92
0
12
Order By: Relevance
“…Tout comme dans cette zone d'étude, de nombreuses études dans le monde et en Côte d'Ivoire en particulier ont mis en évidence l'usage des ressources biologiques des zones humides notamment les forêts marécageuses par les communautés riveraines pour assurer leurs obligations sociales et leur survie dans les domaines de la pharmacopée, l'alimentation, l'artisanat, la construction des habitations, agriculture ; services culturels et autres domaines (Egnankou, 2010 ;Zadou et al, 2011 ;Soro et al, 2014 ;Dargie et al, 2019).…”
Section: Discussionunclassified
“…Tout comme dans cette zone d'étude, de nombreuses études dans le monde et en Côte d'Ivoire en particulier ont mis en évidence l'usage des ressources biologiques des zones humides notamment les forêts marécageuses par les communautés riveraines pour assurer leurs obligations sociales et leur survie dans les domaines de la pharmacopée, l'alimentation, l'artisanat, la construction des habitations, agriculture ; services culturels et autres domaines (Egnankou, 2010 ;Zadou et al, 2011 ;Soro et al, 2014 ;Dargie et al, 2019).…”
Section: Discussionunclassified
“…Nevertheless, it is important to note that some nancially viable but less pro table forest carbon sites will struggle to compete with lucrative land uses, particularly in countries such as Brazil and Indonesia, which are the world's major producers of soy and palm oil, respectively 14 . In other countries, such as the Democratic Republic of the Congo, hydrocarbon exploration and logging developments with multiple vested interests may pose additional barriers to carbon projects 16 . Therefore, it is imperative to implement other conservation strategies and interventions, in addition to carbon nance, to safeguard the carbon stocks and biodiversity in these vulnerable forests.…”
Section: Botswanamentioning
confidence: 99%
“…Common themes seem to be emerging regarding threats to the relatively intact peatlands of Africa and South America. In the Congo Basin, which covers the Republic of the Congo (ROC) and the Democratic Republic of the Congo (DRC), Dargie et al (2018;this issue) indicated the potential threats relating to peatland degradation include infrastructure development and support for hydrocarbon exploration and mining. Both disturbances would require strong policy aimed at the protection of national parks scattered in the region.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Second, evidence-based policy may be formulated, based on the studies in this issue and elsewhere, to allow the design of measures needed to implement national programs and/or Table 4 Summary of options for policy and measures to meet national and subnational agendas that align with the global agenda through adopted international treaties. See Lilleskov et al (2018;this issue) and Dargie et al (2018; NDC, nationally defined contribution; REDD+, reducing emissions from deforestation and forest degradation, and foster conservation, sustainable management of forests, and enhancement of forest carbon stocks; NAMA, nationally appropriate mitigation action specific subnational projects that align with the global climate agenda. Moreover, they may be evaluated to improve the performance and be extrapolated for application elsewhere.…”
Section: Concluding Remarks: Mitigation Strategy Optionsmentioning
confidence: 99%